Increased Binding of von Willebrand Factor to Sub-Endothelial Collagen May Facilitate Thrombotic Events Complicating Bothrops lanceolatus Envenomation in Humans - Olivier Pierre-Louis; Dabor Resiere; Celia Alphonsine; Fabienne Dantin; Rishika Banydeen; Marie-Daniela Dubois; Hossein Mehdaoui; Remi Neviere (Toxins, 2023)
Consumption coagulopathy and hemorrhagic syndrome exacerbated by blood anticoagulability remain the most important causes of lethality associated with Bothrops snake envenomation. Bothrops venom also engages platelet aggregation on the injured endothelium via von Willebrand factor (vWF) interactions. Besides platelet aggregation, some Bothrops venom toxins may induce qualitative thrombopathy, which has been in part related to the inhibition of vWF activation. We tested whether B. lanceolatus venom impaired vWF to collagen(s) binding (vWF:CB) activity. Experiments were performed with B. lanceolatus crude venom, in the presence or absence of Bothrofav, a monospecific B. lanceolatus antivenom. Venom of B. lanceolatus fully inhibited vWF to collagen type I and III binding, suggesting venom interactions with the vWF A3 domain. In contrast, B. lanceolatus venom increased vWF to collagen type VI binding, suggesting the enhancement of vWF binding to collagen at the vWF A1 domain. Hence, B. lanceolatus venom exhibited contrasting in vitro effects in terms of the adhesive properties of vWF to collagen. On the other hand, the antivenom Bothrofav reversed the inhibitory effects of B. lanceolatus venom on vWF collagen binding activity. In light of the respective distribution of collagen type III and collagen type VI in perivascular connective tissue and the sub-endothelium, a putative association between an increase in vWF:CB activity for collagen type VI and the onset of thrombotic events in human B. lanceolatus envenomation might be considered.